Analysis of air conditioning system capacity requirements on the support train - M. Sugiri; Sigit Yulianto; Parman Sinaga; Nadif Abinaya Ramadhani (JTTM : Jurnal Terapan Teknik Mesin, 2025)
Transportation is a fundamental aspect in the economic sector of a country, in terms of supporting economic growth in a country, a quality sustainable mode of transportation is needed to create safe, secure, and comfortable transportation. In order to create a comfortable aspect in the railway transportation mode, namely an air conditioning system that can accommodate thermal comfort in a room. The Rescue Train belonging to the Directorate General of Railways, Ministry of Transportation currently does not use air conditioner as an air conditioning system, therefore researchers conducted research on calculating the capacity requirements of the air conditioning system in the rescue train, the purpose of this research is to determine the total cooling load in the rescue train room using the CLTD (Cooling Load Temperature Difference) method and calculate the Overall Thermal Transfer Value (OTTV) value in the rescue train room to determine the thermal comfort of the building design in the rescue train, the value that can be obtained from the method used in this study is in the form of the Overall Thermal Transfer Value (OTTV) value and the cooling load value of 43.35% of the room area using the CLTD (Cooling Load Temperature Difference) method. The Overall Thermal Transfer Value (OTTV) is 24.4608 W/m², and the total cooling load value using the CLTD (Cooling Load Temperature Difference) method at 43.35% gets a value of 92,912.4372 W (Watt) or 92.91 KW (Kilowatt), so from the calculation of the cooling load at 43.35% of the total area of ​​the helper train, it can be seen that the air conditioner (AC) capacity requirement is 317,017.236 Btu/h or ≈ 79,888.34 kcal/h